Time and sex dependency of hemodynamic, renal, and survivability effects of endotoxemia in rats - Abdalla M. Wedn; Sahar M. El-Gowilly; Mahmoud M. El-Mas (Elsevier, 2020)
Widely different exposure times to endotoxic insults have been employed in reported studies. The current experimental study systematically evaluated the time-course and sex influences of endotoxic insult on survivability and cardiovascular and renal functions. Rats received i.p. lipopolysaccharide (LPS, 5 mg/kg) once or twice (over 2 successive days). Systolic blood pressure (SBP), biomarkers of renal function and inflammation, and vasodilator responsiveness of isolated perfused kidneys to acetylcholine (ACh) or N-ethylcarboxamidoadenosine (NECA) were evaluated 6 hr after first LPS injection or 1, 2, or 6 days later. A single 6-hr LPS challenge caused (i) sex-unrelated elevations in serum urea and creatinine and reductions in NECA, but not ACh, vasodilations, (ii) more increases in renal NF-κB/iNOS expressions in male than in female rats, and (iii) hypotension and tachycardia only in male rats. These parameters, except for hemodynamic changes, were restored to near-control levels 1 day after single LPS dosing. The 2-days dosing with LPS had no effects on renal function biomarkers, but caused hypotension, tachycardia, and increases in renal NF-κB/iNOS expression and NECA and ACh vasodilations in both rat sexes. None of these parameters were different from control values when measured 6 days after the endotoxic insult. Alternatively, the rat mortality was observed during first 2 days of the study and was notably higher in male than in female rats. Our data suggest that the frequency and time elapsed after LPS exposure as well as rat sex are important determinants of the magnitude and direction of detrimental effects of endotoxemia. Keywords: Endotoxemia, Time-course, Sex, Renal, Blood pressure, Inflammation, Mortality